2014
DOI: 10.1021/ie4039357
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and Corrosion Inhibition of Mild Steel in Groundwater at Different Temperatures by Newly Synthesized Benzotriazole and Phosphono Derivatives

Abstract: The corrosion and corrosion inhibition of mild steel in groundwater using 1-(2-pyrrolecarbonyl)-benzotriazole (PBTA) and 1-(2-thienylcarbonyl)-benzotriazole (TBTA) with 2-phosphonoacetic acid (PAA), 4-phosphonobutyric acid (PBA), and Zn2+ at various temperatures ranging from 30 to 60 °C were reported. The study was performed using potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS) along with X-ray diffraction (XRD) and Scanning electron microscopy (SEM) investigations. PDP meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Further, the lm thickness values of root (962.5060Å) and stem (1694.9741Å) were increased due to the chemisorption of inhibitor molecules on mild steel. [33][34][35][36] The obtained lm thickness values are presented in Table 1. The results of Ellipsometer studies revealed that there is excellent chemisorption of C. roseus on the mild steel surface.…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%
“…Further, the lm thickness values of root (962.5060Å) and stem (1694.9741Å) were increased due to the chemisorption of inhibitor molecules on mild steel. [33][34][35][36] The obtained lm thickness values are presented in Table 1. The results of Ellipsometer studies revealed that there is excellent chemisorption of C. roseus on the mild steel surface.…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%
“…When the potential was applied in the direction of anode, then the above reactions were activated leading to the oxide layer formation . This result in the corrosion of the metal surface as shown in : 2Fe+O2+2H2normalO2FeOH2 3FeOH2+0.5O2Fe3O4+30.25emH2normalO …”
Section: Resultsmentioning
confidence: 99%
“…Corrosion inhibition mechanism of BPTA and BPTA synergistic with 0.001 g, of TiO 2 -NP in corrosive environment was demonstrated by the adsorption of BPTA and BPTA synergistic with 0.001 g, of TiO 2 -NP molecules onto the MS surface. The inhibition efficiencies of the BPTA and BPTA synergistic with 0.001 g, of TiO 2 -NP are related to considerable factors such as alloy type, acidic environment, structure of inhibitor including adsorption centers sites, electronic structure, and inhibitor chemical characteristics, interactions type between inhibitor molecules and MS surface [52]. The obtained results (experiments and theoretical), adsorption, different inhibitor molecules may be adsorbed at different sites on the surface of MS.…”
Section: Mechanism Of Corrosion Inhibitionmentioning
confidence: 94%